1987
DOI: 10.5935/0305-7518.19870042
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculoid leprosy in Mexicans is associated with HLA-DR3

Abstract: S ummary HLA-A, B, C, and DR antigens were investigated in a total group of 76 leprosy patients, classified according to the system of Ridley and Jopling in 30 IT and 46 LL individuals. A group of 100 healthy subjects were included for comparison. Patients and controls were all Mexican Mestizos born and inhabitants of Mexico. Typing of blood group systems was also performed. All IT patients showed a positive lepromin skin test, while all LL patients were negative to the specific antigen. The distribution of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 1 publication
1
8
1
Order By: Relevance
“…It was previously demonstrated that, in Mexicans, the HLA-DRB1*03 allele is associated with the TT clinical subgroup (20) and a previous family study demonstrated an association of the HLA-DRB1*1501 allele with LL leprosy (21). In this study, we reported the association of the HLA-DRB1*01 allele with susceptibility to LL and D leprosy and we observed that the HLA-DRB1*08 allele was associated with protection against leprosy.…”
Section: Mb (N=41) Controls (N=99) Mb Vs Controls Hla-dr -----------supporting
confidence: 66%
“…It was previously demonstrated that, in Mexicans, the HLA-DRB1*03 allele is associated with the TT clinical subgroup (20) and a previous family study demonstrated an association of the HLA-DRB1*1501 allele with LL leprosy (21). In this study, we reported the association of the HLA-DRB1*01 allele with susceptibility to LL and D leprosy and we observed that the HLA-DRB1*08 allele was associated with protection against leprosy.…”
Section: Mb (N=41) Controls (N=99) Mb Vs Controls Hla-dr -----------supporting
confidence: 66%
“…HLA-DR3 was associated with tuberculoid leprosy in Mexico 34 and in the South American populations of Surinam 35 and Venezuela, 10 whereas it was found at lower frequencies in lepromatous patients. 35,36 T-cell proliferation responses to certain epitopes of the mycobacterial hsp65 (p3-13) are DR3 restricted 37 and DR3 was associated with low T-cell responses to M. leprae in tuberculoid patients.…”
Section: Class II Regionmentioning
confidence: 90%
“…Earlier studies have reported increased frequencies of HLA-DR2 and DQI in LL patients (2) and of HLA-DR3 in TT (3,4) patients. At the present time the serologically-Characterized HLA antigens can be further subdivided into variants defined by their sequence.…”
Section: Introductionmentioning
confidence: 86%